The Influence of Massage Therapy on Common Complications in Breast Cancer Patient Undergoing Chemotherapy - Bahman Dashtbozorgi; Seyed Mohammad Husseini; Somaye Basak; Seyed Mahmoud Latifi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: Anxiety, depression, nausea and vomiting are the most common side-effects of chemotherapy. This study evaluates the effects of massage therapy on these side-effects of chemotherapy.Subjects and Methods: This clinical trial study was carried out on 34 patients with breast cancer. After being assured that the patients suffering from some degree of depression and anxiety and have nausea and vomiting during previous chemotherapy, they were randomly divided into intervention and control groups. Intervention patients had three sessions back massage in addition to the usual care received. Control group only received usual care. After 24 hr each massage session, a questionnaire was completed. Results: These was significant difference between the two groups suffering from anxiety (P=0.0009, P=0.04, P=0.03) and depression (P=0.03, P=0.03, P=0.01) in 2-4 days, but the difference between nausea (P=0.29, P=0.07, P=0.51) and vomiting (P=0.53, P=0.84, P=0.8) was not statistically significant.Conclusion: Massage therapy is cost effective and readily available it is recommended to be used to reduce anxiety and depression. However, it is not effective in reducing nausea and vomiting.